Review on D-Allulose: In vivo Metabolism, Catalytic Mechanism, Engineering Strain Construction, Bio-Production Technology - Jiang, Suwei; Xiao, Wei; Zhu, Xingxing; Yang, Peizhou; Zheng, Zhi; Lu, Shuhua; Jiang, Shaotong; Zhang, Guochang; Liu, Jingjing (Frontiers in Bioengineering and Biotechnology, 2020)
Rare sugar D-allulose as a substitute sweetener is produced through the isomerization of D-fructose by D-tagatose 3-epimerases (DTEases) or D-allulose 3-epimerases (DAEases). D-Allulose is a kind of low energy monosaccharide sugar naturally existing in some fruits in very small quantities. D-Allulose not only possesses high value as a food ingredient and dietary supplement, but also exhibits a variety of physiological functions serving as improving insulin resistance, antioxidant enhancement, and hypoglycemic controls, and so forth. Thus, D-allulose has an important development value as an alternative to high-energy sugars. This review provided a systematic analysis of D-allulose characters, application, enzymatic characteristics and molecular modification, engineered strain construction, and processing technologies. The existing problems and its proposed solutions for D-allulose production are also discussed. More importantly, a green and recycling process technology for D-allulose production is proposed for low waste formation, low energy consumption, and high sugar yield.